Chlamyweb Study II: a randomised controlled trial (RCT) of an online offer of home-based Chlamydia trachomatis sampling in France. (4th April 2017) - Kersaudy-Rahib, Delphine; Lydié, Nathalie; Leroy, Chloé; March, Laura; Bébéar, Cécile; Arwidson, Pierre; de Barbeyrac, Bertille
Abstract : Background: The number of cases of Chlamydia trachomatis (Ct) diagnosed has increased in the past 15 years in France as well as in other European countries. This paper reports a randomised controlled trial (RCT) to evaluate whether the offer of home-based testing over the internet increased the number of young people tested for chlamydia compared with the current testing strategy and to estimate the number and risks factors of the infected population. This RCT took place as an element of the Chlamyweb Study—a study aiming to evaluate an intervention (the Chlamyweb Intervention) involving the offer of a free self-sampling kit online to sexually active men and women aged 18–24 years in France. Methods: Participants in the Chlamyweb RCT (n=11 075) received either an offer of a free self-sampling kit (intervention group) or were invited to be screened in primary care settings (control group). Risks ratios were used to compare screening rates between the intervention and control groups. Risk factors were analysed for infected people in the intervention group. Results: The screening frequency was about three times higher among young people who received a self-sampling kit than those who only received a tailored recommendation to be screened (29.2% vs 8.7%). Although rates of screening among men were lower than among women (23.9% vs 33.9%), the intervention effect was greater among men (adjusted risk ratios (aRR)=4.55 vs aRR=2.94). Ct positivity (6.8%) was similar to that observed in STI clinics. It was higher in women (8.3%) than in men (4.4%). Conclusions: These results invite us to consider the establishment of a large home-based screening programme, although additional studies including economic assessments are needed to evaluate the most appropriate combination of strategies in the French context. Trial registraion number: AFFSAPS n° IDRCB 0211-A01000-41; Results.